EFFECTIVENESS OF INTERNATIONAL LEGAL SANCTIONS IN THE FIELD OF CIVIL AVIATION AGAINST THE AGGRESSOR STATE - Chulinda, Liudmyla; Savliva, Natalia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the study is to analyze the implementation of international legal sanctions in the field of civil aviation, to find ways to increase the effectiveness of this tool in the context of deterring the aggressor state and correcting its policy. Research methods: in particular, comparative and systematic methods were used to clarify the essence and effectiveness of international legal sanctions, taking into account the huge losses from the full-scale invasion of the Russian Federation on the territory of sovereign Ukraine. Results: it was established that international legal sanctions in the field of civil aviation are aimed at stopping an international offense in order to put pressure on the offending state; it is claimed that joining the international community to their application at the stage of military aggression of the Russian Federation requires a rethinking of the complex of legal relations regarding the adoption and implementation of coercive measures by the UN Security Council and other specialized international organizations; the meaning of international legal sanctions in the field of civil aviation against the aggressor state is determined. Discussion: if a country violates international norms and refuses to fulfill its obligations and take responsibility, it is appropriate to apply sanctions to such a country; sanctions are a tool of long-term action, they can have the maximum political and economic effect after a certain time after their introduction. Conclusion: international legal sanctions are a necessary tool for maintaining justice, restoring the previous state of international relations that existed before the violation of international law based on the principle the rule of international law and the restoration of security and peace.